Differentiation between idiopathic and atypical parkinsonian syndromes using three-dimensional magnetic resonance spectroscopic imaging. Issue 6 (18th January 2013) - Gröger, Adriane; Bender, Benjamin; Wurster, Isabel; Chadzynski, Grzegorz Lukasz; Klose, Uwe; Berg, Daniela
Abstract : Objectives: Degeneration of dopaminergic neurons in the substantia nigra (SN) pars compacta is the primary cause of idiopathic Parkinson's disease (iPD). In early stages of disease in particular, presentation of symptoms is non-specific leading to difficulties in differentiating between iPD and atypical parkinsonian syndromes (aPS). The aim of this study was to evaluate the feasibility of three-dimensional magnetic resonance spectroscopic imaging (MRSI) of the SN region for differentiation between iPD and aPS. Methods: 20 patients with iPD, 10 with aPS and 22 controls were examined on a 3 T MR scanner using three-dimensional MRSI with a voxel size of 0.252 ml and an echo time of 30 ms. Excitation volume was positioned in such a way that in each hemisphere 1 voxel defines the rostral and 1 voxel the caudal SN region. Using a fully automatic spectra evaluation, the metabolite ratios of N-acetyl aspartate/creatine (NAA/Cr) were calculated. Results: In all cases spectra with good quality were obtained. Differences in rostral to caudal NAA/Cr ratios were significant between controls and iPD patients, as well as between iPD and aPS patients (p<0.001 for both). For controls, rostral NAA/Cr was greater than caudal, whereas in iPD patients this ratio was reversed. aPS patients showed similar ratios as controls. Conclusions: Typical reversed rostral to caudal NAA/Cr ratios in iPD patients suggests that they could be linked to specific pathology of neuronal loss in the SN pars compacta. Therefore, the results suggest that MRSI may support the differential diagnosis of patients with clinically unclassifiable parkinsonian syndromes who do not yet fulfil the established clinical criteria.